Quantitation by HPLC-UV of mangiferin and isomangiferin in coffee (Coffea arabica) leaves from Brazil and Costa Rica after solvent extraction and infusion - Trevisan, Maria T.S.; Ulrich, Cornelia; Owen, Robert (Food analytical methods, 2016)
Mangiferin has high potential as a cancer chemopreventive agent; but readily available sources are scarce. Therefore, the concentration of mangiferin and its isomer, were quantitated in the leaves of five species of Coffee leaves from Brazil and Costa Rica respectively. The amount of total mangiferins in methanol extracts of the Brazilian species; was in the range 0.67-4.97 g/kg, whereas in the Costa Rican species, it lay in the range 0.85-4.01 g/kg. In 90 % of cases, mangiferin accounted for 80 % or more of total mangiferins; as opposed to isomangiferin. Infusion studies with powdered leaves of a commercial Brazilian species (Coffea arabica) shows that the release of mangiferins is temperature dependent and that release at 100 °C (1.6 ± 0.06 g/kg) is instantaneous, but approximately 50 % less compared to prolonged methanol extraction (3.05 ± 0.16 g/kg). Consumption of Coffee leaf tea brews, as a natural source of mangiferins, may contribute significantly to elevated intake of these potentially health-promoting phenolic compounds.
Gesehen am 28.02.2018